2021
DOI: 10.1002/advs.202003751
|View full text |Cite
|
Sign up to set email alerts
|

3D Tissue and Organ Printing—Hope and Reality

Abstract: Three-dimensional (3D) bioprinting is an emerging, groundbreaking strategy in tissue engineering, allowing the fabrication of living constructs with an unprecedented degree of complexity and accuracy. While this technique greatly facilitates the structuring of native tissue-like architectures, many challenges still remain to be faced. In this review, the fruits of recent research that demonstrate how advanced bioprinting technologies, together with inspiring creativity, can be used to address these challenges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(42 citation statements)
references
References 97 publications
0
42
0
Order By: Relevance
“…[117] It is also a common strategy to construct vessel networks in 3D bioprinting by using fugitive/sacrificial materials. [204] From blood vessels to the whole heart, Dvir et al [211] also demonstrated the feasibility of personalized hydrogels to print heart with major blood vessels. Certainly, the conditions of 3D bioprinting are much more strict and complex than 3D printing organ models, which is not just adding cells into the printing process.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 4 more Smart Citations
“…[117] It is also a common strategy to construct vessel networks in 3D bioprinting by using fugitive/sacrificial materials. [204] From blood vessels to the whole heart, Dvir et al [211] also demonstrated the feasibility of personalized hydrogels to print heart with major blood vessels. Certainly, the conditions of 3D bioprinting are much more strict and complex than 3D printing organ models, which is not just adding cells into the printing process.…”
Section: Future Perspectivesmentioning
confidence: 99%
“…On the other hand, the future development of 3D printing organ models is not only closely related to the progress of 3D printing technology, but also goes hand in hand with the improvement of printing materials, design tools, process algorithms, and post‐processing techniques. [ 204 ] Furthermore, there is still a lack of a large number of randomized controlled trials to evaluate the effectiveness of organ models. [ 49 , 57 , 192 , 193 ] One of the reasons is that organ models are still difficult to be widely applied.…”
Section: Future Perspectivesmentioning
confidence: 99%
See 3 more Smart Citations